Maximum Power Point Tracking (MPPT) Berbasis Algoritma Human Psychology Optimization (HPO) Untuk Optimalisasi Daya Output Panel Surya Pada Kondisi Partial Shading - Fajar Maulana; Isdawimah Isdawimah; Kusnadi Kusnadi (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2023)
A maximum power point tracking technique (MPPT) based on a metaheuristic algorithm for solar panel systems is proposed, namely MPPT based on the human psychology optimization algorithm (MPPT-HPO). The HPO algorithm has a simple mathematical model that makes it easy to implement in MPPT systems. The proposed MPPT-HPO algorithm is implemented in a solar panel system consisting of 2 solar panels arranged in series and integrated with a DC-DC Boost Converter. The solar panel system was developed by simulation using PSIM software and validated by hardware testing. Solar panel systems equipped with MPPT-HPO were tested under various irradiation conditions, both in non-shading conditions with uniform irradiation and partial shading conditions with non-uniform irradiation. Furthermore, to evaluate its performance, MPPT-HPO is compared with MPPT-PO. The accuracy obtained in testing the MPPT-HPO algorithm is quite good, namely 99% and MPPT-HPO has a stable ability after reaching global maximum power point (GMPP) conditions when compared to the existing MPPT-PO technique